2018
DOI: 10.1590/1414-431x20186962
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-short-term heart rate variability during resistance exercise in the elderly

Abstract: Despite the appeal of ultra-short-term heart rate variability (HRV) methods of analysis applied in the clinical and research settings, the number of studies that have investigated HRV by analyzing R-R interval (RRi) recordings shorter than 5 min is still limited. Moreover, ultra-short-term HRV analysis has not been extensively validated during exercise and, currently, no indications exist for its applicability during resistance exercise. The aim of the present study was to compare ultra-short-term HRV analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 31 publications
0
9
1
1
Order By: Relevance
“…This predictive maximum heart rate (MHR) equation is recognized and applied worldwide 33 . Exercises that fluctuate between 50-60% of the MHR are considered light, between 61-80%, moderate and between 81-90%, intense 34 . Thus, the heart rate oscillation remained on average between 65-83 bpm (<60% MHR), deducing that EAT is a light activity.…”
Section: Discussionmentioning
confidence: 99%
“…This predictive maximum heart rate (MHR) equation is recognized and applied worldwide 33 . Exercises that fluctuate between 50-60% of the MHR are considered light, between 61-80%, moderate and between 81-90%, intense 34 . Thus, the heart rate oscillation remained on average between 65-83 bpm (<60% MHR), deducing that EAT is a light activity.…”
Section: Discussionmentioning
confidence: 99%
“…The use of ultra-short time sequences was investigated in several studies that compared the analysis of ultra-short time measurements with short time measurements demonstrating high correlation between measurements ( 63 65 ). Baek et al ( 66 ) investigated the reliability of this method and concluded that ultra-short time analysis is reliable and comparable to the standard 5-min interval analysis.…”
Section: Methodsmentioning
confidence: 99%
“…The HRV was assessed based on the entire period (2 min), including the fast and slow variation phases of HR during and after exercise (P2 and P3), in line with the previous HRV measurement for wall squat exercise [ 33 ]. As we used an ultra-short-term measurement (<5 min), several HRV indices were selected that are valid for the 2-min measurement, including the standard deviation of normal-to-normal RR intervals (SDNN), the root mean square of successive differences (RMSSD), and the standard deviations of the Poincaré plot (SD1) [ 40 , 41 ]. These HRV indices have also been previously applied in ultra-short-term analysis for exercise, including isometric exercise [ 41 , 42 ].…”
Section: Methodsmentioning
confidence: 99%
“…As we used an ultra-short-term measurement (<5 min), several HRV indices were selected that are valid for the 2-min measurement, including the standard deviation of normal-to-normal RR intervals (SDNN), the root mean square of successive differences (RMSSD), and the standard deviations of the Poincaré plot (SD1) [ 40 , 41 ]. These HRV indices have also been previously applied in ultra-short-term analysis for exercise, including isometric exercise [ 41 , 42 ]. Heart rate recovery (HRR) is an important index for cardiac adaption of exercise.…”
Section: Methodsmentioning
confidence: 99%